Ethics of youth sports: protecting our future - Huston, J. L. (International Journal of Athletic Therapy & Training, 2017)
Youth sports teach lessons of teamwork, perseverance, and competition. The unique aspects of youth sports provide constraints that occur with the interaction between participants, coaches, parents, and medical professionals. Ethical dimensions arise out of the nature of the interaction between adults and youth that can build upon the inherent benefits of youth sports participation or reinforce the worst aspects of participation. Parents and coaches play a particular role in dealing with the development of youth athletes, while medical professionals must understand that the relationship between the patient and clinician and the expectation of the social contract is changed through the dynamics of the triadic nature of healthcare in youth sports.